Impact of single and two-phase dissolved oxygen tension control on Bacillus thuringiensis cultivation and δ-endotoxin production - Mohamed Mazmira Mohd Masri,; Mohd Shawal Thakib Maidin,; Arbakariya Ariff, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Constant δ-endotoxin production is crucial in Bacillus thuringiensis cultivation with aeration strategy playing a significant role in the process. In this study, the impact of DOT control strategies on the cultivation performance of B. thuringiensis was investigated using a 5-L stirred tank bioreactor. Single-phase DOT control recorded low spore count (<5.0 × 1011 spore/mL) and low percentage of sporulation (<45%). Two-stage DOT control cultivation with DOT at 80% during the active growth phase, followed by a switch to 60% or 40% at mid-exponential growth phase contributed to enhanced sporulation (>60%), high maximum cell count (1.5 cfu/mL) with δ-endotoxin formed as early as 8 hr of cultivation. A high maximum specific growth rate, μmax (>0.1 h-1) was also essential in ensuring δ-endotoxin production. High cell count obtained in cultivation with DOT level of 80% saturation during active growth was concurrent with high cell count, high μmax, fast generation time, high OUR, high CER value, and high respiratory quotient (RQ) value. During the two-phase DOT control cultivation, low RQ values were reported. The result showed that the exhaust gas data could be used to monitor B. thuringiensis cultivation performance.